PERANCANGAN KOMIK EDUKASI SOSIAL ISLAMIAH : MAHMUD DAN SHOLEH - BAMBANG BUDIMAN, Dra. Zubaidah, M.Sn., Drs. Syafwan, M.Si. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Al-Qur'an and Al-Hadith are the main source of Islamic teachings and is a reference of Muslims in understanding the Shari'a and teaching how morals as a Muslim. At the present time the lack of media that shows how to behave or morals good in hanging out in the midst of society based on Al-Quran and Al-Hadith, especially in print media that is entertaining and educating like a comic. Comics is one of the visual communication media that has developed rapidly at the present time both published conventionally in print and online.With this comic media is expected to be a new alternative to deliver a message with content that educate about morality socialize fellow Muslims with stories based on Al-Hadith. This comic is titled "Mahmud and Sholeh" through the 5W + 1H analysis method. In addition to media comic media as the main media, this design is supported by several other media such as: x-banner, poster, shirts, stickers, pins, totebag, and mugs that serve as main media supporters and as a media campaign.Keywords: Education, Social, Al-Qur'an, Al-Hadith and Comic.